2020
DOI: 10.1016/j.physletb.2019.135128
|View full text |Cite
|
Sign up to set email alerts
|

Spin projection operators in (A)dS and partial masslessness

Abstract: We elaborate on the traceless and transverse spin projectors in four-dimensional de Sitter and anti-de Sitter spaces. The poles of these projectors are shown to correspond to partially massless fields. We also obtain a factorisation of the conformal operators associated with gauge fields of arbitrary Lorentz type (m/2, n/2), with m and n positive integers.1 In vector notation this reads D a , D b = −2S 2 M ab .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…This in turn demonstrates that the action (2.23) for conformal higher-spin gauge fields factorises, on an AdS 3 background, into wave operators associated with partially massless fields. This is in line with earlier results obtained in even dimensions [20,21,54,[95][96][97][98][99][100][101].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This in turn demonstrates that the action (2.23) for conformal higher-spin gauge fields factorises, on an AdS 3 background, into wave operators associated with partially massless fields. This is in line with earlier results obtained in even dimensions [20,21,54,[95][96][97][98][99][100][101].…”
Section: Discussionsupporting
confidence: 93%
“…The latter are the three-dimensional analogues of the Behrends-Fronsdal traceless and transverse (TT) projectors. Additionally, recent studies [101] in AdS 4 have revealed that the poles of the corresponding TT projectors are intimately related to partially massless fields. This relation renders the factorisation properties of conformal higher-spin wave operators in AdS 4 transparent.…”
Section: Discussionmentioning
confidence: 99%
“…Irreducible supermultiplets of the types (1.5), (1.6) and (1.7) have been used in [28] for the covariant quantisation of the massless supersymmetric higher-spin gauge theories in AdS 4 [16]. The Behrends-Fronsdal projectors have been generalised to the case of AdS 4 only recently in [29]. One of the important outcomes of [29] was a new understanding of the so-called partially massless fields in AdS 4 .…”
Section: B)mentioning
confidence: 99%
“…The Behrends-Fronsdal projectors have been generalised to the case of AdS 4 only recently in [29]. One of the important outcomes of [29] was a new understanding of the so-called partially massless fields in AdS 4 . Such fields in diverse dimensions were studied earlier in [30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: B)mentioning
confidence: 99%
See 1 more Smart Citation